Topics in half integral weight modular forms - Branch, James (2025)
This thesis is divided in three independent chapters. In chapter 1, we prove some explicit results concerning images under Shimura’s map, the methods are elementary. In chapter 2, we provide results on two kernels of half integral weight. Chapter 3 is an exposition to the results obtained as part of the collaboration with Wissam Raji, Larry Rolen and one of my supervisors Nikolaos Diamantis, where we study periods in the half integral weight setting.